'Chariot of Fire': Genre slippages, iconographic agitation and ideological subversion in SRK's Raees. Issue 2 (1st January 2019) - Ahmed, Omar
Genres have often been a safe space for ideological containment, reworking popular conventions and fulfilling audience expectations. But many popular genres including science fiction, horror and the gangster film are also vehicles for subversion. This article will use Raees (Dholakia, 2017), a big budget Bollywood film starring Shah Rukh Khan (SRK), to demonstrate how the Indian gangster film acts as a rejoinder to Hindutva cultural politics, challenging the notion that popular Hindi cinema is merely in the bind of normalizing a nationalist agenda. Using the yatra (procession/journey) sequence as a focal point for textual analysis, I will cover three key areas. This includes the use of political iconography, the violent resistance that emerges to stop the yatra and that is instigated by Raees, a liminal figure of proletarian and secularist ideals, and finally, how the imagining of the Muslim harbours a punitive refrain.